Identification and population genetic studies on Ceratocystis spp. infecting Eucalyptus and Acacia plantations in South Africa and Indonesia - Barnes, Irene (University of Pretoria, 2022)
Dissertation (MSc (Microbiology))--University of Pretoria, 2021.